2016
DOI: 10.1021/acs.langmuir.6b01254
|View full text |Cite
|
Sign up to set email alerts
|

How Does Interfacial Hydration Alter during Rod to Sphere Transition in DDAB/Water/Cyclohexane Reverse Micelles? Insights from Excited State Proton Transfer and Fluorescence Anisotropy

Abstract: How does microscopic organization of an organized assembly alter during macroscopic structural transition? The question may be important to ascertain driving forces responsible for such transitions. Didodecyldimethylammonium bromide (DDAB)/water/cyclohexane reverse micelle is an attractive assembly that undergoes structural transition from rod to spherical shape when the amount of water loading, w0 ([water]/[surfactant]), exceeds a particular value (w0 ∼ 8). Here, we intend to investigate the effect of the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 57 publications
0
36
0
Order By: Relevance
“…They observed ultrafast bulklike ESPT for the centralized HPTS in the AOT RM; however, they found complete suppression of ESPT for the interface-localized HPTS inside of the CTAB RM (Scheme ). Very recently, we explored the ESPT dynamics of HPTS inside of other two cationic RMs: BHDC/benzene/water and DDAB/cyclohexane/water . We found a distinct signature of ESPT and a moderate dependence of ESPT opportunity upon variation in w 0 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They observed ultrafast bulklike ESPT for the centralized HPTS in the AOT RM; however, they found complete suppression of ESPT for the interface-localized HPTS inside of the CTAB RM (Scheme ). Very recently, we explored the ESPT dynamics of HPTS inside of other two cationic RMs: BHDC/benzene/water and DDAB/cyclohexane/water . We found a distinct signature of ESPT and a moderate dependence of ESPT opportunity upon variation in w 0 .…”
Section: Introductionmentioning
confidence: 97%
“…Levinger and co-workers elegantly observed clear cross peaks between HPTS and CTAB surfactant in their 2D NMR spectra . The fluorescence of HPTS is extremely sensitive to the presence of water and has been successfully demonstrated to probe the characteristics of hydration environment inside of micelles, RMs, , and other confined assemblies. , HPTS has weaker acidity in the ground state (p K a 7.2–7.7) and remains primarily in the protonated form in neutral water. , However, electronic excitation abruptly enhances acidity (by ∼7 orders of magnitude) as the p K a * drops to a very low value (0.5–1.4). , Thus, HPTS promptly releases a proton in the excited state if a proton acceptor (e.g., water) is present in the vicinity. Absorption and emission maxima of the protonated (ROH) and deprotonated (RO – ) forms of HPTS are quite distinct, and hence, the excited state proton transfer (ESPT) dynamics could be easily monitored by measuring either transient absorption ,, or time-resolved emission at different wavelengths. , …”
Section: Introductionmentioning
confidence: 99%
“…For example, in anionic sodium bis(2-ethylhexyl)sulfosuccinate (AOT) RMs, the rate of ESPT increases with an increase in the water content ( w 0 ), 3,7 whereas in cationic RMs, the interface-localized probe offers only subtle changes with w 0 . 4,5,16 Lawler et al reported that in AOT RM, the ESPT kinetics of 8-hydroxypyrene-1,3,6-trisulfonate (HPTS) resembles that in bulk water, suggesting a diffusion-controlled power-law time-dependent process, whereas the ESPT rate in nonionic Ig-520 RM shows a slow, two-component model, with one relatively bulk-water-like population and second surface-bound population with a slower lifetime. 3 A few studies have also correlated the solvation dynamics around the ESPT probe and its intramolecular proton transfer dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the scientific basis for the microstructural modification between ACN‐based non‐aqueous RMs with that of aqueous RMs, we have formulated and characterized RMs in cyclohexane (Cy) using didodecyldimethylammonium bromide (DDAB) as the cationic surfactant, by solubilizing water and ACN at different binary compositions. While the double tailed anionic surfactant viz., sodium bis(2‐ethylhexyl) sulfosuccinate (AOT) is one of the most thoroughly utilized for RMs, the double tailed cationic DDAB also can effectively form RMs in nonpolar solvents without a cosurfactant . But surprisingly, it had received relatively less attention from the scientists working in this field.…”
Section: Introductionmentioning
confidence: 99%
“…While the double tailed anionic surfactant viz., sodium bis(2-ethylhexyl) sulfosuccinate (AOT) is one of the most thoroughly utilized for RMs, the double tailed cationic 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 DDAB also can effectively form RMs in nonpolar solvents without a cosurfactant. [11] But surprisingly, it had received relatively less attention from the scientists working in this field. On the other hand, while much attention has been paid so far to the microenvironmental features of ACN-based RMs, relatively less is known about the microstructural properties of the RMs with entrapped ACN and/or water.…”
Section: Introductionmentioning
confidence: 99%